Neuropeptides, Inflammation, Biofilms, and diabetic Foot Ulcers - Yang, Shaoling; Hu, Liye; Han, Rui; Yang, Yiwen (Experimental and Clinical Endocrinology & Diabetes, 2021)
A diabetic foot ulcer (DFU) is a serious complication in patients with diabetes mellitus (DM). A DFU is the most common cause of non-traumatic limb amputation, and patients with DFUs have increased mortality rates within 5 years after amputation. DFUs also increase the risk of cardiovascular and cerebrovascular diseases; therefore, with the increasing incidence and prevalence of diabetic foot wounds, DFUs are gradually becoming a major public health problem. The pathophysiology of DFUs is complicated and remains unclear. In recent years, many studies have demonstrated that the pathophysiology of DFUs is especially associated with neuropeptides, inflammation, and biofilms. Neuropeptides, especially substance P (SP) and calcitonin gene-related peptide (CGRP), play an important role in wound healing. SP and CGRP accelerate the healing of cutaneous wounds by promoting neovascularization, inhibiting the release of certain proinflammatory chemokines, regulating macrophage polarization, and so on. However, the expression of SP and CGRP was downregulated in DM and DFUs. DFUs are characterized by a sustained inflammatory phase. Immune cells such as neutrophils and macrophages are involved in the sustained inflammatory phase in DFUs by extracellular traps (NETs) and dysregulated macrophage polarization, which delays wound healing. Furthermore, DFUs are at increased risk of biofilm formation. Biofilms disturb wound healing by inducing a chronic inflammatory response, inhibiting macrophage phagocytosis and keratinocyte proliferation migration, and transferring antimicrobial resistance genes. To understand the relationships among neuropeptides, inflammation, biofilms, and DFUs, this review highlights the recent scientific advances that provide possible pathophysiological insights into the delayed healing of DFUs.